THE EFFECT OF PROBLEM BASED ELECTRONIC WORKSHEET WITH PROBLEM-BASED LEARNING MODEL ON STUDENT COMPETENCE ACHIEVEMENT IN PHYSICS LEARNING CLASS X SMAS ADABIAH 1 PADANG - Armanda, Berliana Putry; Putra, Amali (Physics Learning and Education, 2024)
In the achievement of students' have at physics competence, it is seen that has not shown optimal results. The causative factor at the learning process students is not active. This condition has happen because students not accustomed to problem soling at physics problems, the teacher is not have any more for giving instructions in the problem solving for physics problems, and lass motivation for students to take part in physics learning at class. Learning physics requires must have resources for learning that all needs for students, one of which is teaching materials. The teaching materials is teaching materials that can make improve student competence in the form of Student Worksheets (LKPD) based problem with problem-based learning models with the advantage by using electronic worksheet. This study aims to determine the effect of problem-based electronic worksheet with problem-based learning model on the physics competency achievement of class X MIPA SMAS Adabiah 1 Padang. This type of research is Quasi Experiment Design with a Randomized Group Only Design. The research population was class X MIPA SMAS Adabiah 1 Padang in the 2022/2023 academic year. The analysis obtained two sample classes are X MIPA 1 and 4. problem-based electronic worksheet with problem-based learning model as for experimental class and X MIPA 4 as a control class using by LKPD at school. The instrument used for knowledge competence is a written test which has been refined through trials and competency skills by assessing student performance. The data obtained was trials and analyzed statistically. The results of the study for both aspects of competency show that classes using electronic worksheet based problem have an average score higher than classes that do not use problem-based electronic worksheet with problem-based learning model. The results of the statistical tests performed showed differences as seen from the data descriptions of the two classes with a significant level of 0.05. The tvalue > ttable , so that it can be concluded that by using the problem-based electronic worksheet students' competence will be better. The effect of the influence exerted by the problem-based electronic worksheet with problem-based learning model on the achievement of students' physics knowledge and skill competencies, respectively, is 65.02% and 73.26%.